Sleep Quality of Functional Gastrointestinal Disorder Patients in Class-Three Hospitals: A Cross-Sectional Study in Tianjin, China. (7th June 2018) - Zhao, Wei; Jin, Hong; Xu, Mengque; Wang, Dongxu; Liu, Yandi; Tang, Yanping; Zhang, Qiuzan; Hua, Jianping; Wang, Bangmao
Abstract : Background . Functional gastrointestinal disorder (FGID) patients are influenced by anxiety, depression, and low sleep quality, which reduce the quality of their life. However, epidemiological data on the quality of sleep in FGID patients were lacking. This study aims to explore the sleep quality and influencing factors of the sleep quality in FGID patients. Methods . 1200 subjects, diagnosed as FGID in one of the six class-three hospitals in Tianjin, China, from January to December 2014, were recruited. The information about demographic information, the severity of clinical symptoms, psychological status (Zung self-rating depression scale), and sleep quality (evaluated with Pittsburgh sleep quality index) was gathered. Results . The questionnaires from 1117 participants were collected including 920 of functional dyspepsia (FD) patients, 77 of irritable bowel disease (IBS) patients, 26 of functional constipation (FC) patients, and 94 other FGID patients. The results showed that morbidity rate for FD patients who had sleep disorders was higher than those who suffered from IBS or FC (P < 0.001 ). The proportion of elderly patients suffering from low sleep quality was higher than that of middle-aged and young patients (P < 0.001 ). The binary logistic regression analysis showed that age, education, and the severity of FGID symptom were influencing factors for poor sleep quality in FGID patients. Conclusion . The issue of poor sleep quality in FGID patients in Tianjin area is prominent, and elderly patients suffer lower sleep quality than other FGID patients. Age, education, and the severity of FGID symptoms are critical influencing factors which result in a drop-in sleep quality.